Patterns of Spiritual Development of Christian Communities in the Social Context of Village Communities: Research at GKII Pondok Daud, Gombolharjo Village - Martono, David; Kaborang, Ndawa (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2025)
Spiritual development in Indonesian rural communities faces unique challenges due to the strong traditional values, especially in Java, which uphold ancestral harmony and traditions. Studies of the spiritual development of Javanese Christian communities in villages are still limited, while previous research has shown that programs that ignore the local cultural context achieve low participation. The study aims to explore the pattern of spiritual development of Christian communities in the village social context, especially the integration of Javanese cultural values with Christian teachings. The research was carried out at GKII Pondok Daud, Gombolharjo Village, a rural community that upholds traditional Javanese values. Using qualitative methods with a flexible ethnographic case study approach allows for an in-depth exploration of the meaning of spiritual formation practices. The research identified four patterns of contextual coaching: (1) direct social approaches through active community involvement; (2) contextual theological strategies to bridge Javanese-Christian spirituality; (3) liturgical-cultural adaptation; (4) contextual Bible immersion. Positive impacts include the growth of the faith of the congregation and interfaith social harmony. Contextual-inclusive spiritual coaching is effective in helping the congregation gain social acceptance while maintaining the integrity of the faith. A model that integrates positive Javanese cultural values with Christian teachings succeeds in creating communities rooted in local culture without losing faith identity.